A wandering Ozurdex in the anterior chamber - Ching-Tai Chen; Shih-Chun Chao; Hung-Yu Lin (Taiwan Journal of Ophthalmology)
Dexamethasone intravitreal implantation (Ozurdex®, Allergan Inc. Irvine, CA, USA) has been used in the treatment of persistent macular edema (ME) due to various vitreoretinal diseases. We described a case of Ozurdex® migration into the anterior chamber. This patient had diabetes mellitus for years and received pars plana vitrectomy due to retinal detachment and anterior chamber intraocular lens implantation due to complicated cataract surgery. We managed this case with surgical intervention without delay and achieved a good effect on complicated corneal edema and previous ME.